Numerical Modelling of Contact Interactionof Profiled Metal Gaskets in Aircraft Flange Connections - Lyubov’ I. Mironova; Oleg A. Kolesnik; Daniil B. Bosak (RUDN Journal of Engineering Research)
The relevance of the research is justified by the development of flange connections of hermetic structures of aeronautical equipment under conditions of weight and material intensity limitation with simultaneous increase of their technical and energetic characteristics. The strength of flange connections is ensured by the reliability of the isolation of the working medium, the tightness of the design elements and is achieved by the use of sealing elements in the form of gaskets or sealing devices. The relevance of the research is stated, the aim of which is the mathematical formalisation of the process of formation of a compacted joint. A brief analysis of known solutions of contact problems by methods of elasticity theory is given, and limitations in obtaining solutions by analytical and numerical methods. A mathematical model of elastic contact between two or more bodies subjected to compression and a numerical solution algorithm based on the FEM method. The algorithm is implemented in the Abaqus CAE software environment. The results of the modelling of the contact interaction of the elements of the sealed joint in the spatial formulation are presented as an example of a full-scale design of a flange joint with a toroidal hollow metal gasket.is a combination of wavelet transformation and neural network learning.